Hillslope erosional features and permafrost dynamics along infrastructure in the Arctic Foothills, Alaska. (18th April 2023) - Stephani, Eva; Darrow, Margaret M.; Kanevskiy, Mikhail; Wuttig, Frank; Daanen, Ronald P.; Schwarber, Jaimy A.; Doré, Guy; Shur, Yuri; Jorgenson, Mark T.; Croft, Peppi; Drage, Jeremiah S.
Abstract: Abrupt thaw of ice‐rich permafrost in the Arctic Foothills yielded to the formation of hillslope erosional features. In the infrastructure corridor, we observed thermal erosion and thaw slumping that self‐healed near an embankment. To advance our understanding of processes between infrastructure and hillslope erosional features (INF‐HEF), we combined climate and remote sensing analyses to field investigations to assess an INF‐HEF system and validate our findings in a broader area along the infrastructure corridor. We identified that thaw consolidation along an embankment formed a thermokarst ditch that was ubiquitous in the broader study area, and which was extensively affected by shrubification and supported other positive feedback (e.g., snow accumulation, water impoundment, and weakened vegetation mat). The thermokarst ditch facilitated channelization of cross‐drainage water, thus increasing the terrain vulnerability to thermal erosion that evolved into thaw slumping after heavy rainfalls. The terrain resilience to thaw slumping benefited from the type of ground ice and topography prevailing at our site. The lateral discontinuity of massive ice in an ice‐wedge polygonal system (i.e., interchange soil and massive ice) compounded to a low‐slope gradient with topographic obstacles (e.g., baydzherakhs) decreased slumping activity and supported self‐stabilization.